Developing the Wair Baluk Well as a Spiritual Tourism Attraction Based on Storynomics in Watukrus Village, Sikka Regency, East Nusa Tenggara Province - Richardus Muga; Michael Rudolfus Sawu; Aurelius Avelinus Dajo (International Journal of Economics, Business and Innovation Research, 2024)
Spiritual tourism has been recognized as an integral part of the global tourism industry because it offers profound spiritual experiences and meanings for tourists. This research aims to analyze the response of the local community, supporting and inhibiting factors to formulate a model for the development of storynomics based spiritual tourism. This study employs a qualitative method with a phenomenological approach. The results show that there is a positive response from the local community towards the development of storynomics based spiritual tourism. However, there are obstacles such as limited local human resources, lack of policies for development, funding for attraction development, and minimal partnerships with external parties. Therefore, modeling is needed to emphasize the importance of building a strong and authentic narrative that involves and motivates stakeholders to actively participate in the development of spiritual tourism. The implications of this research provide valuable insights for tourism practitioners, researchers, and policymakers to enhance the management of storynomics based spiritual tourism by strengthening stakeholder engagement in the development agenda. This model can serve as a foundation for developing sustainable policies and implementation strategies in an effort to achieve holistic and competitive spiritual tourism development.